A facile approach preparing PMMA nanospheres through in-situ surfactant miniemulsion photopolymerization under green LED irradiation. (17th May 2022) - Yu, Siyuan; Zhang, Tianyong; Xing, Jinfeng
Abstract: Herein, a facile method combining in-situ generation of potassium oleate (KOA) and miniemulsion photopolymerization under green LED irradiation was proposed to prepare poly(methylmethacrylate) (PMMA) nanospheres. A miniemulsion containing methyl methacrylate (MMA) was prepared in situ, in which KOA as a surfactant was synthesized by the neutralization reaction of oleic acid (OA) and potassium hydroxide (KOH), and then miniemulsion photopolymerization occurred to obtain PMMA nanospheres under green LED irradiation. Emulsion stability test proved that the in-situ surfactant miniemulsion has higher stability than the preformed surfactant miniemulsion. The effect of surfactant amount and exposure time on photopolymerization was investigated. Furthermore, hexadecane (HD) and polyvinylpyrrolidone (PVP) were introduced into the polymerization system to avoid the adverse effect of Ostwald ripening and particle agglomeration respectively, and PMMA nanospheres with uniform sizes of ∼100 nm were finally prepared. Graphical abstract: Image 1 Highlights: In-situ surfactant and miniemulsion photopolymerization under green LED irradiation were firstly combined. In-situ KOA method can obtain a miniemulsion with longer shelf life. ∼100 nm of uniform PMMA nanospheres can be obtained under photopolymerization for 30 min.